Sonic Signatures in South African Jazz: A stylistic analysis of the trio music of Kyle Shepherd, Bokani Dyer and Nduduzo Makhathini - de Villiers, Melorie Jane (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMus)--Stellenbosch University, 2021.